PERBANDINGAN KUALITAS CITRA RADIOGRAFI DIGITAL ANTARA HASIL DIGITISASI FRAME GRABBER DAN COMPUTED RADIOGRAPHY - , SITI DARYATI ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Comparative on image quality has been done for digital fluoroscopic radiography a frame grabber (DFR) and by a computed radiography (CR) and its relation to the entrace skin exposure (ESE) value. ESE measurement was using free in air method by a personal alarm dosimeter. The phantom object of antromorphic phantom pelvis was used. Digitization process was using a frame grabber that was connected to the output of a fluoroscopy imaging system. Results from digital fluoroscopy using DrGrabber was compared to the results from CR. Contrast analysis based on histogram and line profile was using ImageJ software. The ESE value for CR and digitized by the frame grabber increased as the voltage increased. The ESE value of CR lowest 54.35 ± 2 and highest 111.36 ± 2 while The ESE value of DFR lowest 17.48 ± 1 and highest 117.45 ± 2. The ESE value of DFR (quartil 1 = 30,60 mR, quartil 2 = 49,60 mR and quartil 3 = 78,01 mR)was lower than the ESE value of CR (quartil 1 = 61,10 mR, quartil 2 = 74,69 mR and quartil 3 = 90,55 mR). These results are lower than the quartil 1, 2, dan 3 of ESE value for abdomen AP diagnostic of AAPM Report No.31 (2005). The voltage increase in CR provided no contrast difference based on color gradation, while a better contrast difference are obtained by DFR.